Mary Astell : theorist of freedom from domination - Springborg, Patricia (Cambridge University Press, 2005)
Philosopher, theologian, educational theorist, feminist, and political pamphleteer, Mary Astell was an important figure in the history of ideas. This study addresses the apparent paradoxes between her often radical views and position as a Royalist High Church Tory, recovering the historical and philosophical contexts for her thought.